2018
DOI: 10.23970/ahrqepccer208
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for Bipolar Disorder in Adults: A Systematic Review

Abstract: Purpose of Review• To assess the effectiveness of drug and nondrug therapies for treating acute mania or depression symptoms and preventing relapse in adults with bipolar disorder (BD) diagnoses, including bipolar I disorder (BD-I), bipolar II disorder (BD-II), and other types. Key Messages• Acute mania treatment: Lithium, asenapine, cariprazine, olanzapine, quetiapine, risperidone, and ziprasidone may modestly improve acute mania symptoms in adults with BD-I. Participants on atypical antipsychotics, except fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 77 publications
(229 reference statements)
0
16
0
2
Order By: Relevance
“…Food and Drug Administration approved anticonvulsants for the treatment of bipolar disorder in adults; they are carbamazepine, valproate, lamotrigine [176].…”
Section: Other Mood Stabilizersmentioning
confidence: 99%
“…Food and Drug Administration approved anticonvulsants for the treatment of bipolar disorder in adults; they are carbamazepine, valproate, lamotrigine [176].…”
Section: Other Mood Stabilizersmentioning
confidence: 99%
“…Although MDD is more prevalent in the population, antipsychotics are particularly effective and commonly started during the acute phase of mania in BD [13]. Despite the fact that evidence on the long-term effectiveness and safety of antipsychotics in these episodic and remitting disorders is limited, many patients remain on antipsychotics chronically and perhaps unnecessarily [3,11,12,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In our study population, we found that the most prevalent mental health disorders were depression and anxiety, with the former substantially exceeding county estimates in males (14.1 vs. 12.5%, p = 0.0047). Furthermore, while county level data were not available, our patients appeared to have higher rates of both bipolar disorder (3.5 vs. 2–3%) (4244) and schizophrenia (2.5 vs. 0.4%) (45) compared to national estimates in the general population. These findings agree with previous studies that have indeed suggested that the overall rate of psychiatric disorders is elevated amongst both the uninsured (46) as well as the homeless (47, 48).…”
Section: Discussionmentioning
confidence: 54%